Darwin Koenig letter to James J. Dinsmore regarding summer bird sightings, July 31, 1997 - Koenig, Darwinet al (1997)
Letter from Darwin Koenig to James J. Dinsmore regarding summer bird sightings, July 31, 1997. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1997. Epson - sheet feed